2015
DOI: 10.3758/s13414-014-0780-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental state attribution and the gaze cueing effect

Abstract: Theory of mind is said to be possessed by an individual if he or she is able to impute mental states to others. Recently, some authors have demonstrated that such mental state attributions can mediate the Bgaze cueing^effect, in which observation of another individual shifts an observer's attention. One question that follows from this work is whether such mental state attributions produce mandatory modulations of gaze cueing. Employing the basic gaze cueing paradigm, together with a technique commonly used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
110
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(136 citation statements)
references
References 67 publications
15
110
7
Order By: Relevance
“…As we suggested in the Introduction, we have set up an experiment in which the spontaneous perspective taking theory can be falsified. These data are also consistent with our previous observation that changes in perspective do not modulate the gaze-cueing effect (Cole, Smith, & Atkinson, 2015). The results of our direct tests contrast with many previous studies that have indirectly assessed spontaneous ToM processes.…”
Section: Discussioncontrasting
confidence: 55%
“…As we suggested in the Introduction, we have set up an experiment in which the spontaneous perspective taking theory can be falsified. These data are also consistent with our previous observation that changes in perspective do not modulate the gaze-cueing effect (Cole, Smith, & Atkinson, 2015). The results of our direct tests contrast with many previous studies that have indirectly assessed spontaneous ToM processes.…”
Section: Discussioncontrasting
confidence: 55%
“…Nonetheless, neither photographic faces nor dynamic movement in gaze cues have been shown to increase the magnitude of the gaze cueing effect with adults (Hietanen & Leppänen, 2003). Recent work has even revealed that gaze cueing in a live face-to-face situation elicits an effect comparable in magnitude to schematic eye gaze stimuli (Cole, Smith, & Atkinson, 2015;Lachat, Conty, Hugueville, & George, 2012). Interestingly, however, some evidence suggests that social manipulations of the gazecueing effect may be most powerful under conditions where gaze stimuli are dynamic and thus better approximates experience of gaze in the environment.…”
Section: Attending To Action In Interactive Contextsmentioning
confidence: 99%
“…Research on gaze cueing has involved a wide range of experimental set-ups and stimuli. Some have used schematic faces (Friesen & Kingstone, 1998), others images of real faces (Driver et al, 1999) and some have even used real people (Cole, et al 2015). However, what is the appropriate level of abstraction?…”
Section: Issues Of Ecological Validity?mentioning
confidence: 99%